The Liver X Receptor Agonist TO901317 Ameliorates Behavioral Deficits in Two Mouse Models of Autism - Cai, Yulong; Zhong, Hongyu; Li, Xin; Xiao, Rui; Wang, Lian; Fan, Xiaotang (Frontiers in Cellular Neuroscience, 2019)
Autism spectrum disorder (ASD) is a developmental disability characterized by social deficits and repetitive stereotyped behaviors. There are currently no drugs available for the treatment of the core symptoms of ASD, suggesting an urgent need for new therapeutic strategies. The neurobiology of autism is complex, but emerging research indicates that defects in hippocampal neurogenesis are associated with ASD in both humans and mouse models of ASD, leading to the suggestion that restoring neurogenesis may be a novel therapeutic approach for ASD. Here, we found that postnatal treatment with TO901317 (TO), a potent liver X receptor (LXR) agonist, typically activated LXRβ and its target genes in the hippocampus, and alleviated the social deficits and stereotypical behaviors in BTBR T+ tf/J (BTBR) and valproic acid (VPA)-induced mouse models. In addition, we further confirmed that TO postnatal treatment also rescued the inhibition of adult hippocampal neurogenesis in these two models. In summary, our study suggests that LXR agonist targeting hippocampal neurogenesis may represent a novel potential therapy for ASD.